Legal Analysis of Administrative Sanctions Against Hospitals Failing to Meet Accreditation Requirements - A.Nugroho; D.Permadi (The Medical Journal of Hospital Management and Health Law, 2026)
The quality of healthcare services is intrinsically linked to the enforcement of institutional standards, primarily maintained through hospital accreditation. This study investigates the legal implications and the enforcement of administrative sanctions against hospitals that fail to meet these mandatory accreditation requirements. Employing a normative juridical research method, this study analyzes relevant statutory legislation, ministerial regulations, and authoritative legal doctrines to evaluate the efficacy and consistency of administrative penalties. The results indicate that while the legal framework provides a structured tier of sanctions—ranging from written warnings to the revocation of operational licenses—the enforcement mechanism faces significant challenges, particularly concerning the continuity of public healthcare access and regulatory ambiguities. The discussion reveals a critical gap between theoretical legislative intent and practical enforcement, highlighting how the immediate closure of non-compliant hospitals can inadvertently jeopardize local patient care. The study integrates a comprehensive literature review on administrative law and medical jurisprudence to contextualize these findings within contemporary healthcare governance. In conclusion, this study suggests that administrative sanctions must be applied through a balanced approach that prioritizes patient safety without abruptly disrupting public health infrastructure. It recommends the establishment of an intermediate regulatory oversight body and clearer transitional guidelines to assist struggling hospitals in achieving compliance before ultimate punitive measures are executed.